Comparative analysis of lignocellulosic component in straw and husk of MR219 and MR263 by rapid chemical analysis - Naqiya F.M.Z.; Azean Y.; Razis S.; Nurul-Era-Amira H.; Fazry S.; Airianah O.B. (Penerbit Universiti Kebangsaan Malaysia, 2017)
Lignocellulosic materials comprise cellulose, hemicelluloses, lignin and others component such as pectins and protein. However, the content and composition of these components vary, depending on plant species, variety, plant growth and development condition, which are influenced by season and geographical location. In this study, the lignocellulosic component of straw and husk of MR219 and MR263, the main paddy varieties planted in Malaysia were chemically extracted and quantitatively evaluated via spectrophotometric method. The lignin content in the straw and husk of MR219 are 7.21% and 9.50%, respectively. While the the lignin within straw and husk of MR263 are 8.17% and 10.21%, respectively. The cellulose content in all samples is between 38.20% and 42.63%. On the other hand, the hemicellulose percentage in straw samples (7.14% – 9.57%) is lower as compared to husk (22.97% – 32.43%), for both MR219 and MR263. In conclusion, the lignocellulosic composition and content of paddy biomasses are able to be determined by rapid chemical extraction method and it is demonstrated that the paddy chemical lignocellulosic composition depends on paddy variety and parts.